Experience-focused thinking and cognitive mapping in ethical banking practices: from practical intuition to theory - Ferreira, F. A. F. (2017)
Concern over ethical management and ethical principles in banking practices is rapidly increasing. The alignment of such concerns with daily operations, however, is often far from simple. This study proposes the use of cognitive mapping to enhance our understanding of the key factors underlying ethical banking and the manner in which they inter-relate with each other. Cognitive mapping provides a process for the integration and representation of a group of experts' experience-focused thinking, and as such allows for the development of a well-informed methodological framework. By depicting the cause-and-effect linkages among determinants of ethical banking, and analyzing them in a holistic way, such a map not only serves as a support for the integration of values, ethics and banking, but can help create theory, based on experts' practice in this field.